2021
DOI: 10.1186/s12884-021-03691-y
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of pregnant women during COVID-19 pandemic: a descriptive phenomenological study

Abstract: Background With the onset of the COVID-19 epidemic, pregnancy and childbirth for women are taking place in unusual circumstances. We explored the lived experiences of pregnant women during the COVID-19 pandemic to better understand their experience of pregnancy so that better support could be provided. Methods We used a descriptive phenomenological approach to understand the lived experience of pregnant women in COVID-19 pandemic. We collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
91
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 35 publications
(28 reference statements)
12
91
0
10
Order By: Relevance
“…Several studies have now looked at the experiences of pregnant and postnatal women globally, and while their experiences are specific to their location and the timeframe in the pandemic that the research was carried out, recurrent themes are emerging. As with the women in our study, anxiety and fear [ 14 , 20 24 ] were commonly reported as was the need for reliable information [ 22 24 ]. In one study of perinatal anxiety in the USA, 60% of women reported moderate or severe anxiety symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies have now looked at the experiences of pregnant and postnatal women globally, and while their experiences are specific to their location and the timeframe in the pandemic that the research was carried out, recurrent themes are emerging. As with the women in our study, anxiety and fear [ 14 , 20 24 ] were commonly reported as was the need for reliable information [ 22 24 ]. In one study of perinatal anxiety in the USA, 60% of women reported moderate or severe anxiety symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 74%
“…In a study in Italy, which was the epicenter of the pandemic in Europe in the early stages, women with a history of anxiety or depression were at a higher risk of anxiety symptoms or post-traumatic stress disorder during “lockdown” than those without[ 13 ]. Disruption to antenatal and postnatal care was seen all over the world [ 24 , 26 – 28 ]; however the degree of disruption varied according to the resources, or lack of resources, in that particular country. Low- and middle-income countries are particularly vulnerable to the disruption of routine maternal and neonatal care [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other concerning issues are the emotional, physical, and mental exhaustion and loss of medical staff, the shortage of essential hygiene equipment, the varieties of symptoms and secondary diseases caused by the infection, and the failure of many proposed treatments [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies have assessed women's experiences of pregnancy during the COVID-19 pandemic [35,36,37], studies conducted in Wales are lacking. In addition, there are a lack of studies examining experiences of pregnancy during the pandemic in combination with national data on objective measures of neonatal and obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%